2016
DOI: 10.1080/87565641.2016.1167212
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Between Impulsivity, Anxiety, and Risk-Taking and the Neural Correlates of Attention in Adolescents

Abstract: Although impulsivity, anxiety, and risk-taking may relate to attentional processes, little research has directly investigated how each may be associated with specific facets of attentional processes and their underlying neural correlates. Nineteen adolescents performed an fMRI task involving simple, selective and divided attention. Out-of-scanner-assessed impulsivity, anxiety and risk-taking scores were not correlated with each other and showed task-phase-specific patterns of association. Results are discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 100 publications
1
3
0
Order By: Relevance
“…27 In addition, our findings could also be seen through the different dose-response curves for cognitive and behavioral changes 47 and the possibility that different neurobiological mechanisms underlie the attention and inhibition systems, 48 but especially that the ADHD pathophysiology reflects an abnormal interchange in large-scale brain circuits, 49 where the precise relationship between these functions (such as for impulsivity and attention functions) remains incompletely understood. 50 We did not observe any differences in response due to different ADHD subtypes, which confirms previous reports. 12,47 The heterogeneity in the causes and presentations of ADHD, 4,20 inter-individual variability in neurotransmitters, 4 and different cognitive profiles, 7 may be reflected in the variability of the response to MPH found in our study, although no evidence of differences in the response to MPH was seen for different clinical subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…27 In addition, our findings could also be seen through the different dose-response curves for cognitive and behavioral changes 47 and the possibility that different neurobiological mechanisms underlie the attention and inhibition systems, 48 but especially that the ADHD pathophysiology reflects an abnormal interchange in large-scale brain circuits, 49 where the precise relationship between these functions (such as for impulsivity and attention functions) remains incompletely understood. 50 We did not observe any differences in response due to different ADHD subtypes, which confirms previous reports. 12,47 The heterogeneity in the causes and presentations of ADHD, 4,20 inter-individual variability in neurotransmitters, 4 and different cognitive profiles, 7 may be reflected in the variability of the response to MPH found in our study, although no evidence of differences in the response to MPH was seen for different clinical subtypes.…”
Section: Discussionsupporting
confidence: 91%
“…We expected the outcome should be an increased drive toward irrelevant stimuli and a reduced inhibition of irrelevant responses, which could be important in explaining the attentional deficit and impulsivity of ADHD (Bonaventura et al., 2017). The decreased reactivity to non‐rewarded‐ or aversive‐related stimuli should translate into low levels of harm avoidance and anxiety are reported to be associated with risky activities such as hazardous driving, gambling, and substance abuse (Baker & Galvan, 2020; Elsey et al., 2016; Nash et al., 2021; Peris & Galvan, 2021; Wills et al., 1994). Thus, our findings may provide a causal model for the link between D 4.7 repeats polymorphism and specific personality traits such as novelty‐seeking and risk‐taking.…”
Section: Discussionmentioning
confidence: 99%
“…Although performance deficits in some of these attentional tasks may stem from smoking-associated working memory impairments (Jacobsen et al, 2005 , 2007c ), findings from neural correlate studies conducted in smoking and non-smoking youth suggest that smoking behaviors impact the development and function of attentional brain circuits. Many studies have shown morphological and functional differences between smoking and non-smoking adolescents in the prefrontal cortex (PFC), inferior parietal cortex, and anterior insula that in part comprise the selective and divided attention neural circuits (Elsey et al, 2016 ). Gray matter loss in the cortex may be exacerbated by smoking; smokers reportedly have lower amounts of gray matter in the frontal cortex (Li et al, 2015 ; Akkermans et al, 2017 ; Chaarani et al, 2019 ), inferior parietal lobe (Li et al, 2015 ; Akkermans et al, 2017 ), and insula (Li et al, 2015 ) than non-smoking controls, and gray matter in the dorsolateral PFC (DLPFC) was negatively correlated with smoking dependency (Li et al, 2015 ).…”
Section: Tobacco and E-cigarettesmentioning
confidence: 99%